Mifepristone Treatment Promotes Testicular Leydig Cell Tumor Progression in Transgenic Mice - Ponikwicka-Tyszko D; Chrusciel M; Pulawska K; Bernaczyk P; Sztachelska M; Guo PL; Li XD; Toppari J; Huhtaniemi IT; Wolczynski S; Rahman NA (MDPI, 2022)
Simple SummaryRecently, the antiprogestin activity of selective progesterone receptor (PR) modulator mifepristone (MF) has proven unsuccessful as a potential anti-cancer agent in various clinical trials. Herein, we analyzed the effects of MF treatment on Leydig cell tumor (LCT) progression in a transgenic mouse model (inhibin-alpha promoter-driven SV40 T-antigen), as well as on the proliferation of two Leydig tumor cell lines. MF significantly stimulated the proliferation of LCT in vitro. Similarly, a 1-mo MF or P4 treatment stimulated LCT tumor growth in vivo. Only the abundant membrane Pgrmc1 expression was found in LCTs, but no other classical Pgr or nonclassical membrane PRs. Functional analysis showed that PGRMC1 is required for MF and P4 to stimulate the proliferation and invasiveness of LCTs. Our findings provide novel information that the use of MF as an anti-cancer agent should be considered with caution due to its potential PGRMC1 tumor-promoting pathway activation in cancers.The selective progesterone receptor modulator mifepristone (MF) may act as a potent antiproliferative agent in different steroid-dependent cancers due to its strong antagonistic effect on the nuclear progesterone receptor (PGR). Hereby, we analyzed the effects of MF treatment on Leydig cell tumor (LCT) progression in a transgenic mouse model (inhibin-alpha promoter-driven SV40 T-antigen), as well as on LCT (BLTK-1 and mLTC-1) cell proliferation. MF significantly stimulated the proliferation of LCT in vitro. Similarly, a 1-mo MF or P4 treatment stimulated LCT tumor growth in vivo. Traceable/absent classical Pgr or nonclassical membrane PRs alpha, beta, gamma and Pgrmc2, but abundant membrane Pgrmc1 expression, was found in LCTs. MF did not activate glucocorticoid or androgen receptors in LCTs. Functional analysis showed that PGRMC1 is required for MF and P4 to stimulate the proliferation and invasiveness of LCTs. Accordingly, MF and P4 induced PGRMC1 translocation into the nucleus and thereby stimulated the release of TGF beta 1 in LCT cells. MF and P4 treatments upregulated Tgfbr1, Tgfbr2, and Alk1 expression and stimulated TGF beta 1 release in LCT cells. Our findings provide novel mechanistic insights into the action of MF as a membrane PR agonist that promotes LCT growth through PGRMC1 and the alternative TGF beta 1 signaling pathway.